Symptom-associated change of motor-related neuromagnetic fields in a patient with multiple sclerosis: A case report. (April 2018) - Kim, Ji Hee; Kim, Bong Soo; Hwang, Su Jeong; Chang, Won Seok; Kim, Ki Woong; Kwon, Hyuk Chan; Lee, Yong Ho; Chang, Jin Woo
Highlights: The lower amplitude of the readiness field and decreased the equivalent current dipole strength of the movement-evoked observed in affected hemisphere during motor weakness had recovered after symptom improvement in patient with multiple sclerosis. Neurophysiologic activities related to movement using magnetoencephalography may be used to detect diffuse functional changes in the brain that are not observable by conventional imaging of white matter regions in multiple sclerosis. Neuromagnetic field analysis may allow us to better understand MS pathology not only in focal lesions, but also in the normal-appearing white and grey matter. Abstract: The objective of this study was to investigate functional abnormalities of the brain in a patient with multiple sclerosis (MS) by using magnetoencephalography (MEG) and a finger-tapping task. A 46-year-old woman that presented with motor weakness of left hand and was diagnosed with MS. Conventional magnetic resonance imaging demonstrated a white matter lesion with hyperintensity on T2-weighted images in the right motor area. MEG recordings were performed during the period of motor weakness and after clinical improvement. Neuromagnetic brain activation was elicited by a simple, visually cued finger movement. The Equivalent current dipole (ECD) strength of the movement-evoked field (MEF) in the affected hemisphere was significantly decreased relative to the unaffected hemisphere. After improvement in motor weakness, we found that the lower amplitude of the readiness field and decreased ECD strength of the MEF observed in affected hemisphere during motor weakness had recovered. Analysis of motor-related neuromagnetic fields revealed that MEG may be used to detect diffuse changes in the brain that are not observable by conventional imaging of white matter regions in MS. We further found that brain activities can change after improvement in motor weakness.